Layer-by-layer-assembled microfiltration membranes for biomolecule immobilization and enzymatic catalysis - Smuleac, V (Langmuir : the ACS journal of surfaces and colloids, 2006)
Multilayer assemblies of polyelectrolytes, for protein immobilization, have been created within the membrane pore domain. This approach was taken for two reasons: (1) the high internal membrane area can potentially increase the amount of immobilized protein, and (2) the use of convective flow allows uniform assembly of layers and eliminates diffusional limitations after immobilization. To build a stable assembly, the first polyelectrolyte layer was covalently attached to the membrane surface and inside the pore walls. Either poly(L-glutamic acid) (PLGA) or poly(L-lysine) (PLL) was used in this step. Subsequent deposition occurs by multiple electrostatic interactions between the adsorbing polyelectrolyte [poly(allylamine) hydrochloride (PAH) or poly(styrenesulfonate) (PSS)] and the oppositely charged layer. Three-layer membranes were created: PLL-PSS-PAH or PLGA-PAH-PSS, for an overall positive or negative charge, respectively. The overall charge on both the protein and membrane plays a substantial role in immobilization. When the protein and the membrane are oppositely charged, the amount immobilized and the stability within the polyelectrolyte assembly are significantly higher than for the case when both have similar charges. After protein incorporation in the multilayer assembly, the active site accessibility was comparable to that obtained in the homogeneous phase. This was tested by affinity interaction (avidin-biotin) and by carrying out two reactions (catalyzed by glucose oxidase and alkaline phosphatase). Besides simplicity and versatility, the ease of enzyme regeneration constitutes an additional benefit of this approach